The protective effects of insulin on the developing of dementia in chronic kidney disease patients with hypertension and diabetes: a population-based nationwide study - Yun-Yi Chen; Yi-Hsien Chen; Yu-Wei Fang; Jing-Tong Wang; Ming-Hsien Tsai (BMC Nephrology)
Abstract Background Chronic kidney disease (CKD), hypertension, and diabetes are associated with dementia, and insulin resistance promotes vascular dysfunction resulting in dementia. However, the study of insulin use in preventing dementia in CKD patients with diabetes and hypertension is limited. We aim to assess the effects of insulin use on the incidence of dementia in patients with CKD with hypertension and diabetes. Design, setting and participants A retrospective cohort study using the nationwide database from Taiwan’s National Health Insurance Research Database. We selected 11,758 CKD patients with diabetes and hypertension in 2006, including 5,864 insulin users and 5,894 non-insulin users. Moreover, their medication possession ratios (MPR) were calculated. Main outcomes We used the competing risk model to estimate the hazard ratio (HR) for the incidence of dementia for insulin use in the target population. Results In a follow-up period of 11 years, 1285 events of dementia were recorded, and the multivariate-adjusted HR for dementia by insulin usage (yes vs. no) and insulin usage per MPR is 0.652 (95% confidence interval [CI]: 0.552 to 0.771) and 0.995 (95% CI: 0.993 to 0.998) respectively. Such a significant negative association was consistent in almost all subgroups. Moreover, a dose-dependent effect of insulin was noted, where patients with higher insulin MPRs were less likely to have dementia. Conclusion The CKD patients with hypertension and diabetes who received insulin therapy had a 35% decreased risk of dementia.